Conceptual design of glass/renewable natural fibre-reinforced polymer hybrid composite motorcycle side cover - Wahab, Mafa; Salit, Mohd Sapuan; Moklis, Muhammad Harussani; Mohamed Yusoff, Mohd Zuhri; A. A., Saleh (Tech Science Press, 2021)
This paper presents the development process relating to the conceptual design of glass/renewable natural fibre-reinforced polymer hybrid composite motorcycle side cover. Motorcycle side cover is a component frequently made from plastic or steel that functions on covering the motorcycle parts, components and systems such as frame, battery, electrical systems and mechanical systems. Function Analysis Systems Techniques (FAST) is used to identify the functions of motorcycle side cover. The right-side cover of motorcycle model SYM E-Bonus 110 has been physically studied to identify the competitive benchmarking criteria. The functions and competitive benchmarking criteria are then compiled and integrated with the environmental requirements to identify the Product Design Specifications (PDS). The coir fibre has been selected from six identified dominant renewable natural fibre used for automotive component through integration of Ranking Method and Quality Based Selection (QBS). Then the polypropylene matrix is selected after shortlisting the existing thermoplastic that is used with coir fibre and has high suitability for injection moulding manufacturing. The polypropylene matrix is then evaluated using Weighted Evaluation Matrix (WEM) by comparing to benchmark material which is Acrylonitrile Butadiene Styrene (ABS). After that, the conceptual design development of glass/renewable coir fibre-reinforced polypropylene motorcycle side cover is carried out using an integrated Theory of Inventive Problem Solving (TRIZ) and Morphological Chart, followed by final conceptual design selection using integration of Pugh Scoring Method and QBS. The conceptual design development intended on improving the biodegradability to reduce pollution to the environment. However, the usage of glass/coir fibre-reinforced polypropylene hybrid composite may increase the weight due to higher density. Four innovative design concepts have been developed and the selected final concept design has the most minimum number of ribs and minimum thickness with the same ratio of glass fibre and natural fibre composition.